2018
DOI: 10.1007/s00203-018-1496-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of fungal isolates and hatching success of green turtle (Chelonia mydas) nests

Abstract: The aim of this study is to investigate the fungal diversity of green turtle nests and to examine phylogenetic relationships among these isolates. During the nesting season, samples of intra-nest sand and failed eggs were collected from 25% of the surviving nests in Sugözü Beaches, which are amongst the most important nesting beaches for endangered green turtles in the Mediterranean. Twenty-three fungi were identified by molecular techniques. Fungal isolates belonged to genera Aspergillus, Emericella, Rhizopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Additionally, Bailey et al (2018) demonstrated the presence of Fusarium DNA (F. falciforme and F. keratoplasticum) in embryonic fluid and biofilms from 73 fully incubated, unhatched loggerhead sea turtle eggs collected from different regions of North America. However, a recent molecular study from Turkey identified fungi from five genera (Aspergillus, Emericella, Rhizopus, Actinomucor and Apophysomyces) isolated from successfully hatched green turtle (Chelonia mydas) nests on eastern Mediterranean coasts (Candan, 2018). Moreover, these authors demonstrated that the hatching success of nests contaminated by fungi was significantly lower than those of uncontaminated nests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Bailey et al (2018) demonstrated the presence of Fusarium DNA (F. falciforme and F. keratoplasticum) in embryonic fluid and biofilms from 73 fully incubated, unhatched loggerhead sea turtle eggs collected from different regions of North America. However, a recent molecular study from Turkey identified fungi from five genera (Aspergillus, Emericella, Rhizopus, Actinomucor and Apophysomyces) isolated from successfully hatched green turtle (Chelonia mydas) nests on eastern Mediterranean coasts (Candan, 2018). Moreover, these authors demonstrated that the hatching success of nests contaminated by fungi was significantly lower than those of uncontaminated nests.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of Gram-positive bacteria, the most frequently isolated species of staphylococci from C. mydas nests in Costa Rica were Staphylococcus aureus, Staphylococcus intermedius, Staphylococcus epidermidis and Staphylococcus cromogenes (Santoro et al, 2006). Those fungal species isolated from sea turtle nests and eggs come from Aspergillus, Fusarium, Chrysosporium, Penicillium, Emericella, Rhizopus, Actinomucor and Apophysomyces genera (Bailey et al, 2018;Candan, 2018;Güçlü et al, 2010;Phillott et al, 2002). These genera are predominantly saprophytic species that become opportunistic pathogens under particular conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Species in the FSSC are not the only fungi found to penetrate sea turtle egg shells. For example, Candan ( 2018 ) also identified several species of Aspergillus, Emericella, Rhizopus, Actinomucor , and Apohysomyces in the nests of living green turtles using molecular methods. There are reports of fungal pathogens of sea turtles in many parts of the world, including Australia, North America, South America, Asia, Europe and Africa ( Table 1 ).…”
Section: Other Species Of Fungi Infecting Sea Turtlesmentioning
confidence: 99%
“…This value was found higher on other green turtle nesting beaches such as Akyatan 76% [19], Kazanlı 82.9% [20], Samandağ 69.9% [25], Northern Cyprus 84.2% [26]. Hatching success can be influenced by fungal infections [27], moisture [28] and clutch size [29]. However, [30] concluded that environmental factors they examined were not correlated with hatching success.…”
Section: Figure 2 the Spatial Distribution Of Nests On The Yeniyurt Nesting Beachmentioning
confidence: 99%